EVALUASI PENYELENGGARAAN PENDIDIKAN DI PERGURUAN TINGGI: RELEVANSI BIDANG PEKERJAAN DENGAN PROGRAM STUDI - Karunia Eka Lestari; Marsah Rahmawati Utami; Mokhammad Ridwan Yudhanegara (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2021)
This qualitative descriptive study aims to evaluate the implementation of education in higher education by observing the relevance of the graduate's occupation with the Study Program. The data analyzed is tracer study data obtained from the Career Development Division at one of the leading higher education in Indonesia. The data records 2561 profiles of graduates from the 2010 batch, and 1566 of them have jobs in various fields, while the other 995 graduates are unemployment or continuing their studies. Data analyzed by performing correspondence analysis. The output of this method produces a graphical display of the data in a correspondence plot. The plot displays information about the association's structure between the relevance of the graduate's occupation and the Study Program. The result shows that 69.97% of graduates have jobs that are relevant to the field of study, with the most corporation area (16%), specifically in the industry field (category C), and the most job description (22%) in the research and development division. The results of this study, in general, can be used as recommendations in evaluating the implementation of education in higher education, especially in managing career development programs for graduates.